Congenital Myasthenic Syndrome and AChR Mutation - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2000)
A 20-year-old woman from a consanguineous Moroccan marriage, with progressive muscle weakness noted from 2 years of age and evaluated at the University of Bonn, Germany, was found to have congenital myasthenic syndrome (CMS) due to homozygosity of the 1293insG e-acetylcholine receptor subunit mutation.